The Role of the Library in Enhancing the Information Literacy of Students at Madrasah Aliyah Negeri 1 Medan - Winda Listiyani; Irwasnsyah Irwasnsyah; Indira Fatra Deni PA (Sean Institute, 2026)
This study aims to determine the role of the library in improving students' information literacy at State Islamic Senior High School (MAN) 1 Medan and to identify the benefits students obtain from various information literacy services and programs organized by the library. The study uses a descriptive method with a quantitative approach. The study population was all 500 students of class XII of MAN 1 Medan, while the research sample was 83 respondents determined using incidental sampling techniques based on the Slovin formula. Data collection techniques were carried out through observation, questionnaire distribution, and documentation studies, while the data were analyzed using descriptive statistics in the form of frequency distribution and percentages. The results of the study indicate that the role of the library in improving students' information literacy is in the good category with an average value of 3.18. Various efforts made by the library, such as providing information services, collections that suit user needs, library education, information search guidance, and the use of online catalogs (OPAC), have made a positive contribution to students' abilities in finding, selecting, evaluating, organizing, and utilizing information effectively. In addition, the benefits felt by students from the implementation of the information literacy program also obtained an average value of 3.18 with a good category, which indicates that the library is able to support the fulfillment of students' information needs while supporting the learning process in the madrasah environment. Thus, the MAN 1 Medan library has played an optimal role as a center for learning resources and a center for information literacy, so it is necessary to continue to develop more innovative and sustainable services, collections, and literacy programs to improve the quality of students' information literacy in the digital era.